Scriptores Ordinis Cartusiensis: Tomus Primus. 2 volumes. By Dom Stanislas Autore. Transcribed and arranged by Jean Picard. Pp. iv + 257 and ii + 141. (Analecta Cartusiana, 200:4 and 5.) Salzburg: Institut für Anglistik und Amerikanistik, 2005. isbn 3 900033 21 8 and 22 6. Paper €40 each - Gribbin, Anselm J. (The journal of theological studies, 2006)
TheScriptores Sacri Ordinis Cartusiensis by Dom Stanislas Autore (1853–1920), who died at the now defunct Charterhouse of Naples, appeared in the Analecta Cartusiana as a facsimile edition of the original manuscript (AC 120, 20 vols.). This important work, the fruit of many years of research, contains alphabetical lists featuring anonymous Carthusian writers and identifiable authors and scribes—with biographical information—and includes spiritual and liturgical works, correspondence, details of manuscripts, and writings in print. At the time of publication (1993–5) ‘Tomus Primus’ of the Scriptores, listing authors and copyists from A to C, was lost, but it was fortunately rediscovered and reproduced in 2003 (AC 200:1–3).